Tocqueville and the frontiers of democracy - Boyd, Richard, 1970-; Atanassow, Ewa. (Cambridge : Cambridge University Press, 2013)
'This collection of essays uses Alexis de Tocqueville's writings as a jumping-off point to explore the dilemmas of democratization in the twenty-first century'--
Machine generated contents note: Acknowledgments; Short title key to works cited; Introduction: Tocqueville and the frontiers of democracy Ewa Atanassow and Richard Boyd; Part I. The Meaning of Democracy and the Democratic Revolution: 1. Democracy and revolution in Tocqueville: the frontiers of democracy Nestor Capdevila; 2. The frontier between democracy and aristocracy Ran Halevi; 3. Tocqueville's Burke, or story as history Ralph Lerner; Part II. Democratization in a Non-Western Context: 4. Tocqueville and religion: beyond the frontier of Christendom Alan Kahan; 5. Deliberating democratization with Tocqueville: the case of East Asia Cheryl Welch; 6. Tocquevillean thoughts on higher education in the Middle East Joshua Mitchell; Part III. Challenges of Globalization: Democracy, Markets, and Nationhood: 7. Tocqueville and the unsettled global village Susan McWilliams; 8. Nationhood: democracy's frontier? Ewa Atanassow; 9. Commerce, glory, and empire: Montesquieu's legacy Celine Spector; Part IV. Democracy, Imperialism, and Foreign Policy: 10. The surprising M. Tocqueville: necessity, foreign policy, and civic virtue David Clinton; 11. Democracy and domination: empire, slavery, and democratic corruption in Tocqueville's thought Jennifer Pitts; 12. Tocqueville and the Napoleonic legend Richard Boyd; Part V. Democracy's Old and New Frontiers: 13. Tocqueville, the problem of equality, and John Ford's Stagecoach Robert Pippin; 14. The poetry of democracy Paul Berman; 15. Tocqueville and the local frontiers of democracy Robert T. Gannett, Jr; Epilogue: new frontiers, old dilemmas Richard Boyd; List of contributors; Bibliography; Index.
Keywords: Tocqueville, Alexis de, -- 1805-1859. -- Political and social views; Democracy